2020
DOI: 10.3389/fnhum.2020.00057
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Differences in Cortical Activation During Action Observation, Action Execution and Interpersonal Synchrony: An fNIRS Study

Abstract: Interpersonal synchrony (IPS) is an important everyday behavior influencing social cognitive development; however, few studies have investigated the developmental differences and underlying neural mechanisms of IPS. functional near-infrared spectroscopy (fNIRS) is a novel neuroimaging tool that allows the study of cortical activation in the presence of natural movements. Using fNIRS, we compared cortical activation patterns between children and adults during action observation, execution, and IPS. Seventeen sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 85 publications
2
23
0
Order By: Relevance
“…Using fMRI, researchers have found greater activation during action imitation or execution compared to observation [ 40 , 42 , 44 ]. These findings echo the results of our past fNIRS study of interpersonal synchrony in healthy adults and children [ 22 , 23 ]. Together, these results suggest that the challenges of imitation or interpersonal synchrony stem from the complexity of motor control components and not the observation component.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Using fMRI, researchers have found greater activation during action imitation or execution compared to observation [ 40 , 42 , 44 ]. These findings echo the results of our past fNIRS study of interpersonal synchrony in healthy adults and children [ 22 , 23 ]. Together, these results suggest that the challenges of imitation or interpersonal synchrony stem from the complexity of motor control components and not the observation component.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, we compared the behaviors and associated cortical activation between interpersonal synchrony and its component behaviors (i.e., action observation and execution). Our past findings in adults and typically developing children show that the neural complexity of imitation/interpersonal synchrony arises from the motor component and not the perceptual component [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…First, the fNIRS device focused on the pre-frontal cortex and could not perform whole brain assessment and was not able to assess deeper neuroanatomical structures [26]. Second, our sample size was small but was comparable with previous fNIRS studies [11,27,28]. Third, due to limitation of time and consistency, this study only involved one cognitive task (i.e., arithmetic tasks) and did not include other cognitive tasks (e.g., verbal fluency test, trail making task), and further research is required to assess the effect brief relaxation practice on other cognitive tasks.…”
Section: Discussionmentioning
confidence: 89%
“…The results also implicate other brain regions including the supplementary motor region (SMA) [37] or superior/middle temporal gyri [30]. Recent studies with developing population have found consisting cortical activation patterns [38,39]. When comparing execution and observation, studies have reported that observing someone perform an action seems to elicit more bilateral activation than executing the same action in the superior/middle temporal gyri, STS, vPMC and somatosensory region [30,31].…”
Section: Introductionmentioning
confidence: 76%